Improving Letters Memorize Ability Through the Alphabet Box Media Using the Playing Method - Dhita Paranita Ningtyas; Agung Cahya Karyadi; Sabila Amalia Utami; Yula Milshteyn (Edutechnium Journal of Educational Technology, 2023)
The ability to memorize letters of the alphabet is an early readiness in children's reading skills. This study aims to improve the ability to memorize alphabet letters in group A TK Kuncup Melati. In development activities, the researcher prepares several alphabet box media to hone children's ability to memorize letters. The use of learning media significantly encourages a learning activity's success in achieving developmental aspects. Therefore, development activities require appropriate learning media for children, namely creative, innovative media that can attract children's learning interests. The method used in this study is a class action research method. The research was conducted in cycles, each consisting of planning, implementing, observing, and reflecting. The results of this reflection are used as a basis for making improvements, processes, and results in the next cycle. Of the 19 students consisting of 14 girls and five boys, there was an increase after improvements and actions were made in cycle I, the average percentage obtained was 65% because it had not yet reached the average limit of achievement in a study, namely 75%, then the second cycle of research was carried out and showed an average presentation of 86%, that is, children's learning outcomes were more than 75%. Based on the results of research on increasing the ability to memorize letters of the alphabet through the alphabet box media using the play method, it shows that there is an increase in children's ability to memorize letters of the alphabet with correct pronunciation and children can arrange letters or words using the alphabet box media. So that means the teacher must continue developing the learning media and provide varied activities for children.